(3YOe GdJejjR Hjf GdQLd h GdeQCI ai GdYed (B/ s - (3Ydi MSf EHQGgje YeGQIs; (3CMeO MSf GdHQYis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2011)
(3JTcd gPg GdOQGSI GfWdGbI dHjGf ChLg YOe GdJejjR Hjf GdQLd h GdeQCI(B: (3h LhGfH GdMeGjI GdbGfhfjI ddeQCI GdYGedI aj GdJTQjY GdebGQf(B: (3JfGhdfG ajgG GdeSGhGI h YOe GdJejjR Hjf GdQLd h GdeQCI aj eLGd GdYed(B: (3GhVMfG ajg GdhVYjI GdJGQjNjI ddeQCI(B. (3aj GdMVGQGJ GdeNJdaI(B: (3GdJYQja HeHOC GdeSGhGI Hjf GdLfSjf aj eLGd GdYed(B: (3JfGhdJ GdOQGSI GdLghO GdOhdjI defGgVI GdJejjR Hjf GdQLd h GdeQCI aj eLGd GdYed(B: (3ef NdGd LghO GdCee GdeJMOI h efXeI GdYed GdOhdjI h GdJTQjYGJ GdebGQfI(B: (3YQVfG GdLghO GdYQHjI defGgVI GdJejjR ef NdGd LghO cd ef efXeI GdYed GdYQHjI h GdJTQjYGJ GdYQHjI h GdhWfjI GdJj fXeJ GdeSCdI efgjf Edi GdfJGFL h GdJhUjGJ GdJj CSaQJ YfgG GdOQGSIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdGLJeGYjI, (B2011s
(3HHdjhLQGajG(B: (3UaMGJ (B438-457s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJTQjYGJ GdELJeGYjIs; (3CLhQ efNaVIs; (3GdeSGhGIs; (3YOe GdJejjRs; (3JGQjN Yed GdeQCIs; (3JMQjQ GdeQCIs; (3eHOC GdeSGhGI s; (3eYGjjQ GdYed GdOhdjIs; (3efGgVI GdJejjRs; (3Shb GdYeds; (3JOGHjQ GdMeGFjI ddeQCI GdYGedIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs